Intensive care unit visiting and family communication during the COVID-19 pandemic: A UK survey. (August 2022) - Boulton, Adam J; Jordan, Helen; Adams, Claire E; Polgarova, Petra; Morris, Andrew Conway; Arora, Nitin
Background: Frequent visiting and communication with patients' families are embedded within normal ICU practice, however the COVID-19 pandemic has challenged this, and it is unclear how ICUs are managing. We aimed to investigate how NHS ICUs are approaching family communications and visiting during the COVID-19 pandemic. Methods: An electronic snapshot survey was delivered between 16th April and 4th May 2020 and was open to NHS ICUs. Replies from 134 individual ICUs with COVID patients were included. Results: All reported that visiting was more restricted than normal with 29 (22%) not allowing any visitors, 71 (53%) allowing visitors at the end of a patient's life (EOL) only, and 30 (22%) allowing visitors for vulnerable patients or EOL. Nearly all (n = 130, 97%) were updating families daily, with most initiating the update (n = 120, 92%). Daily telephone calls were routinely made by the medical (n = 75, 55%) or nursing team (n = 50, 37%). Video calling was used by 63 (47%), and 39 (29%) ICUs had developed a dedicated family communication team. Resuscitation and EOL discussions were most frequently via telephone (n = 129, 96%), with 24 (18%) having used video calling, and 15 (11%) reporting discussions had occurred in person. Clinicians expressed their dissatisfaction with the situation and raised concerns about the detrimental effect on patients, families, and staff. Conclusions: COVID-19 has resulted in significant changes across NHS ICUs in how they interact with families. Many units are adapting and moving toward distant and technology-assisted communication. Despite innovative solutions, challenges remain and there may be a role for local and national guidance.